Sun up, sun down : the story of day and night - Bailey, Jacqui; Lilly, Matthew (Minneapolis, MN : Picture Window Books, 2004)
Follows the sun from dawn to dusk to explain how light rays travel, how shadows are formed, how the moon lights up the night sky, and more.
Includes index.
Book Links (A.L.A.)
School Library Journal
Wilson's Children
Book Links (A.L.A.), March 2009
School Library Journal, August 2004
Keywords: Day -- Juvenile literature; Night -- Juvenile literature; Day; Night; Day; Night; Earth -- Rotation -- Juvenile literature; Sun -- Juvenile literature; Earth -- Rotation; Moon; Sun; Earth; Moon; Sun